Flow Injection Chemiluminescence Determination of Acetylsalicylic Acid in Pharmaceutical Formulations - Jabbar, Hijran S. (Science Journal of University of Zakho, 2016)
A simple and sensitive flow injection chemiluminescence method was proposed for the determination of acetylsalicylic acid (aspirin) in pharmaceutical formulations. The method was based on inhibition effect of acetylsalicylic acid on the chemiluminescence reaction of luminol–hydrogen peroxide and potassium hexacyanoferrate. Different experiment parameters affecting the chemiluminescence intensity were carefully studied and incorporated into the procedure. The detection limit was 0.5 μg/mL of acetylsalicylic acid, and chemiluminescence emission intensity was correlated with the drug concentration in the range 2.5-125 μg/mL with correlation coefficient of 0.9985 and analytical frequency of 75 determinations per hour. The results obtained for the assay of pharmaceutical formulations were compared well with those obtained by the official method in British Pharmacopoeia and demonstrated good accuracy and precision.
Keywords: Flow Injection; Chemiluminescence; Acetylsalicylic Acid; Luminol-Hydrogen Peroxide; Potassium Hexacyanoferrate; Pharmaceuticals